Lung function and atherosclerosis: a cross‑sectional study of multimorbidity in rural Uganda - Gilbert, Rebecca F.; Cichowitz, Cody; Bibangambah, Prossy; Kim, June‑Ho; Hemphill, Linda C.; Yang, Isabelle T.; Sentongo, Ruth N.; Kakuhikire, Bernard; Christiani, David C.; Tsai, Alexander C.; Okello, Samson; Siedner, Mark J.; et al. (BMC Pulmonary Medicine, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is a leading cause of global mortality. In high-income settings, the presence of cardiovascular disease among people with COPD increases mortality and complicates longitudinal disease management. An estimated 26 million people are living with COPD in sub-Saharan Africa, where risk factors for co-occurring pulmonary and cardiovascular disease may differ from high-income settings but remain uncharacterized. As non-communicable diseases have become the leading cause of death in sub-Saharan Africa, defining multimorbidity in this setting is critical to inform the required scale-up of existing healthcare infrastructure. Methods: We measured lung function and carotid intima media thickness (cIMT) among participants in the UGANDAC Study. Study participants were over 40 years old and equally divided into people living with HIV (PLWH) and an age- and sex-similar, HIV-uninfected control population. We fit multivariable linear regression models to characterize the relationship between lung function (forced expiratory volume in one second, FEV1) and pre-clinical atherosclerosis (cIMT), and evaluated for effect modification by age, sex, smoking history, HIV, and socioeconomic status. Results: Of 265 participants, median age was 52 years, 125 (47%) were women, and 140 (53%) were PLWH. Most participants who met criteria for COPD were PLWH (13/17, 76%). Median cIMT was 0.67 mm (IQR: 0.60 to 0.74), which did not differ by HIV serostatus. In models adjusted for age, sex, socioeconomic status, smoking, and HIV, lower FEV1 was associated with increased cIMT (β = 0.006 per 200 mL FEV1 decrease; 95% CI 0.002 to 0.011, p = 0.01). There was no evidence that age, sex, HIV serostatus, smoking, or socioeconomic status modified the relationship between FEV1 and cIMT. Conclusions: Impaired lung function was associated with increased cIMT, a measure of pre-clinical atherosclerosis, among adults with and without HIV in rural Uganda. Future work should explore how co-occurring lung and cardiovascular disease might share risk factors and contribute to health outcomes in sub-Saharan Africa
Keywords: COPD; Cardiovascular disease; HIV infection; FEV1; cIMT; Uganda